Peran Modal Manusia terhadap Upah Pekerja di Kota Makassar - Rusydi, Bahrul Ulum; Wahab, Abdul; Budiastuti, Dwi (Bulletin of Economic Studies (BEST), 2021)
Human capital is a basic element in the progress of economic development, and superior human beings are believed to be a fundamental factor in determining the level of income of the population of a country or region. This study aims to determine the effect of human capital variables on workers' wages in Makassar City. The variable are total population, school participation rate, and net enrollment rate. To analyze this effect, multiple regression models are used with the ordinary least square (OLS) method. The results show that the total population has a significant effect on worker wages, while the school participation rate and net enrollment rate do not have a significant effect on worker wages. Consistent government efforts are needed to boost school enrollment rates and net enrollment rates. This effort is expected to be one of the factors in increasing the quality of the population so as to increase worker productivity in Makassar City. Keywords: Human Capital, Worker’s Wage, OLS, Makassar City Modal manusia merupakan elemen dasar dalam kemajuan pembanguan ekonomi, dan manusia yang unggul diyakini sebagai faktor yang fundamental dalam menentukan tingkat pendapatan penduduk suatu negara maupun wilayah. Penelitian ini bertujuan untuk mengetahui pengaruh dari variabel-variabel modal manusia terhadap upah pekerja di Kota Makassar. Adapun variabel yang dimaksud antara lain Jumlah Penduduk, Angka Partisipasi Sekolah, dan Angka Partisipasi Murni. Untuk menganalisis pengaruh tersebut digunakan model regresi berganda dengan metode ordinary least square (OLS). Hasil penelitian menunjukkan bahwa Jumlah Penduduk berpengaruh signifikan terhadap Upah Pekerja, sedangkan Angka Partisipasi Sekolah dan Angka Partisipasi Murni tidak berpengaruh signifikan terhadap Upah Pekerja. Perlu upaya pemerintah yang konsisten untuk memacu angka partisipasi sekolah, dan angka partisipasi murni. Upaya tersebut diharapkan dapat menjadi salah satu faktor dalam peningkatan kualitas penduduk sehingga dapat meningkatkan produktivitas pekerja di Kota Makassar Kata kunci: Modal Manusia, Upah Pekerja, OLS, Kota Makassar